2020
DOI: 10.1111/ppc.12580
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of web‐based distance education for parents in the prevention of emotional neglect and abuse: A randomized controlled study

Abstract: The aim of this study was to determine the efficacy of web-based distance education for the prevention of child emotional neglect and abuse by increasing parental awareness of emotional abuse and appropriate attitudes toward child-rearing.Design and Methods: This study had a quasi-experimental, randomized controlled design. The study sample included a total of 60 parents who had taken their child to a pediatric outpatient clinic in Turkey. Of 60 parents, 30 were randomly assigned to an experimental group and 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Gulirmack et al, a study aimed at effectiveness of web-based distance education for parent in the prevention of emotional abuse and neglect, categorized the information needed to design web-based application into seven sections: familiarity with child abuse, mental health in children, parental behavioral characteristics, reward and punishment for children, parenting skills, and parent demographic characteristics [ 35 ]. According to the approach they pursued to identify educational content, the present study collected educational content in seven sections: familiarity with child abuse, child behavioral disorders, parental behavioral skills, parenting skills, child abuse prevention, child rights protection organizations and child abuse laws in Iran.…”
Section: Discussionmentioning
confidence: 99%
“…Gulirmack et al, a study aimed at effectiveness of web-based distance education for parent in the prevention of emotional abuse and neglect, categorized the information needed to design web-based application into seven sections: familiarity with child abuse, mental health in children, parental behavioral characteristics, reward and punishment for children, parenting skills, and parent demographic characteristics [ 35 ]. According to the approach they pursued to identify educational content, the present study collected educational content in seven sections: familiarity with child abuse, child behavioral disorders, parental behavioral skills, parenting skills, child abuse prevention, child rights protection organizations and child abuse laws in Iran.…”
Section: Discussionmentioning
confidence: 99%
“…Parents fail to provide shelter, clothing, nutrition, safety, health, protection, education or care for their children (Gülırmak & Orak, 2021).…”
Section: (D) Neglectmentioning
confidence: 99%
“…For instance, it has been found that child abuse can interfere with the development of children’s emotion regulation and interpersonal relationships, undermine their self-esteem, and induce feelings of shame and inadequacy (Longobardi et al, 2022). As depicted in Table 1, child abuse falls into four categories: psychological abuse (B1), physical abuse (C1), sexual abuse (D1), and neglect behavior (E1) (Azzopardi et al, 2019; Gülırmak & Orak, 2021; Sarkar et al, 2020; Scoglio et al, 2021; Wu et al, 2022). There are some inconsistent findings in the global prevalence of the different forms of child abuse.…”
Section: Conceptualization Of Child Abuse and Aggressive Behaviormentioning
confidence: 99%
“…D2: Any nonconsensual, unwanted, or exploitative sexual activity that involved children less than 18 years of age (Azzopardi et al, 2019). (E) Neglect Behavior E1*: The failure of parents to provide nutrition, shelter, clothing, health, education, protection, care, and safety for a child (Gülırmak & Orak, 2021). E2: The failure of parents to meet their children's basic needs (J.…”
Section: Association Between Child Abuse and Aggressive Behaviormentioning
confidence: 99%